1969
DOI: 10.1136/bmj.3.5673.738
|View full text |Cite
|
Sign up to set email alerts
|

Association between Foeto-maternal Bleeding and Hypertension in Pregnancy

Abstract: S ummary: A blind prospective survey of foetomaternal bleeding in 200 primiparous pregnancies was carried out in an investigation of a possible association between foeto-maternal bleeding and hypertension in pregnancy.Evidence of foeto-maternal bleeding was found in 61% of 36 hypertensive pregnancies, and in 51% of 160 normotensive pregnancies, a difference which is not statistically significant.Significant differences between the hypertensive and the nermotensive groups were found when foeto-maternal bleeding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1970
1970
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…A ®rst step in the direction of being able to quantify the extent of feto-maternal bleeding was the development of a staining technique which permitted a distinction to be made between fetal and maternal erythrocytes (Kleihauer et al, 1957). Using this technique, it could be shown that the occurrence of fetal erythrocytes was indeed more frequent in pregnancies affected by pre-eclampsia than in healthy controls (61 versus 51%) (Jones et al, 1969). However, this effect was most dramatic in samples taken before 36 weeks pregnancy, where signi®cant differences in the numbers of fetal erythrocytes were noted in those pregnancies subsequently affected by pre-eclampsia, in contrast to those with normal deliveries.…”
Section: Fetal Cell Traf®c In Pre-eclampsiamentioning
confidence: 99%
“…A ®rst step in the direction of being able to quantify the extent of feto-maternal bleeding was the development of a staining technique which permitted a distinction to be made between fetal and maternal erythrocytes (Kleihauer et al, 1957). Using this technique, it could be shown that the occurrence of fetal erythrocytes was indeed more frequent in pregnancies affected by pre-eclampsia than in healthy controls (61 versus 51%) (Jones et al, 1969). However, this effect was most dramatic in samples taken before 36 weeks pregnancy, where signi®cant differences in the numbers of fetal erythrocytes were noted in those pregnancies subsequently affected by pre-eclampsia, in contrast to those with normal deliveries.…”
Section: Fetal Cell Traf®c In Pre-eclampsiamentioning
confidence: 99%
“…The subjects were 110 primigravidae who, as part of another investigation (Jones, 1969), were being carefully supervised during pregnancy. As a group they had the advantage that their folate stores could not have been affected by a previous pregnancy.…”
mentioning
confidence: 99%
“…This vital aspect was subsequently confirmed by the use of the then novel Kleihauer-Betke stain, which permitted the detection of fetal erythrocytes in maternal blood samples (11). This indicated that their proportion was indeed greater in pregnancies affected by pre-eclampsia (12). These data thereby provided further insight into the placental lesion in pre-eclampsia, indicating that it involved both increased trophoblast shedding, as well as leakage of fetal blood cells across the villous barrier (2, 3).…”
Section: Fmm and Pre-eclampsia: Historical Observationsmentioning
confidence: 91%